2016
DOI: 10.18632/oncotarget.8621
|View full text |Cite
|
Sign up to set email alerts
|

Implication of comorbidity on the initiation of chemotherapy and survival outcomes in patients with locoregionally advanced nasopharyngeal carcinoma

Abstract: BackgroundTo assess the impact of comorbidity on the initiation of chemotherapy and its ultimate treatment outcomes in patients with locoregionally advanced nasopharyngeal carcinoma (NPC).MethodsData on 1316 patients with NPC treated between February 2003 and January 2007 was retrospectively reviewed. Comorbidity was assessed using the Adult Comorbidity Evaluation-27 (ACE-27) system. The association of various factors with chemotherapy was evaluated. And treatment outcomes of chemoradiotherapy regimes in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…In this study of elderly patients with NPC receiving definitive RT, we found that, when using the CCI score as a measure of medical comorbidities, significant comorbidities were present in 22.4% of patients. Previous studies have reported the incidence of comorbidity in patients with NPC to be 40.2–58% . Ramakrishnan et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study of elderly patients with NPC receiving definitive RT, we found that, when using the CCI score as a measure of medical comorbidities, significant comorbidities were present in 22.4% of patients. Previous studies have reported the incidence of comorbidity in patients with NPC to be 40.2–58% . Ramakrishnan et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, comorbidity was present in 40.1% of patients. The incidence of comorbidity in lrNPC patients is similar to that in primary NPC patients ( 17 ). However, patients with moderate and severe comorbidities were observed to have higher rates of comorbidity than primary NPC.…”
Section: Discussionmentioning
confidence: 61%
“…Next, the incidence of comorbidities significantly increased with age in this sort of cancer [20]. Patients with comorbidities were more likely to experience undertreatment, and comorbidity itself indicated poor prognosis in locoregionally advanced NPC [20]. Besides, older patients were found to be those had higher titer of VCA-IgA and EA-IgA and diagnosed with more advanced clinical stage (Table 1).…”
Section: Discussionmentioning
confidence: 94%
“…Considering the inferior outcome of concurrent chemotherapy with cisplatin below 200 mg/m 2 [19], older patients possibly achieved poor survival. Next, the incidence of comorbidities significantly increased with age in this sort of cancer [20]. Patients with comorbidities were more likely to experience undertreatment, and comorbidity itself indicated poor prognosis in locoregionally advanced NPC [20].…”
Section: Discussionmentioning
confidence: 94%